A STUDY ON ETHICAL PRACTICES OF PUBLIC SECTOR BANKS IN THIRUVANANTHAPURAM DISTRICT - J C, Augustin John; Sreekanth, G. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The bank is now a larger and representative institution for the protection of funds and financial of the society. A banker performs many more task than mere regular and conventional banking. As such the role and status of the banker in the modern society has changed significantly. When the banker has acquired a new status and role in the society it should perform the duty in a more diligent and appropriate manner. The performance of the duty has a definite relationship with the kind of ethical practices, values, and system The present study was undertaken the ethical practices of public sector banks in Thiruvananthapuram district. The study mainly focuses on the importance of ethical practices and value building exercise in organizations. The proper functioning of an organization requires various rules and regulations, principles and policies. Due to different type and nature of organizations, the policy formulation and problem solving strategy differs from one organization to other. However, in every work place, the organization adopts a set of rules and policies which are essential for its growth and development. Among various factors, the implementation and adhering to ethical practice and value building is the main foundation for the regulation of organization. Yet, to examine factors as to understand the implication of ethics and value practice in an organization are complex in nature.